Cellular and Molecular Characterization of Microglia: A Unique Immune Cell Population - Sousa, Carole; Biber, Knut; Michelucci, Alessandro (Frontiers in Immunology, 2017)
Microglia are essential for the development and function of the adult brain. Microglia arise from erythro-myeloid precursors in the yolk sac and populate the brain rudiment early during development. Unlike monocytes that are constantly renewed from bone marrow hematopoietic stem cells throughout life, resident microglia in the healthy brain persist during adulthood via constant self-renewal. Their ontogeny, together with the absence of turnover from the periphery and the singular environment of the central nervous system, make microglia a unique cell population. Supporting this notion, recent genome-wide transcriptional studies revealed specific gene expression profiles clearly distinct from other brain and peripheral immune cells. Here, we highlight the breakthrough studies that, over the last decades, helped elucidate microglial cell identity, ontogeny, and function. We describe the main techniques that have been used for this task and outline the crucial milestones that have been achieved to reach our actual knowledge of microglia. Furthermore, we give an overview of the “microgliome” that is currently emerging thanks to the constant progress in the modern profiling techniques.